Family Support for Controlling Blood Pressure of Elderly Patients in Health Facilities During the Covid-19 Pandemic in Banjarmasin - Tutpai, Gertrudis; Unja, Ermeisi Er; Nura, Florentina (KnE Life Sciences, 2021)
At the time of writing, Covid19 cases were steadily increasing in Banjarmasin. Elderly people were afraid to go to the health facilities to control their blood pressure because they were afraid of catching this disease. However, checking blood pressure in the elderly with hypertension is extremely important, and in the absence of qualified medical staff their families need to take on the role. This research is to find the correlation between family support and controlling blood pressure of elderly patients in health facilities. This study was a quantitative research with cross sectional design that used documentation sheets and questionnaires about family support. Selected via purposive sampling, 50 people from families with hypertension were included in this study. The research period was May to July 2020. Data analysis used Chi Square test at